Community Structure Analysis of The Boroko and Binuanga Mangrove Areas North Bolaang Mongondow Regency, North Sulawesi Province - SM, Farid; Mohamad, Nurdin; Salihi, Irvan Abraham; Wantogia, Misnawaty; Kumaji, Syam S.; Utina, Ramli; Hasim, Hasim; Baderan, Dewi Wahyuni K. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangrove forests are one of the potential coastal and marine natural resources that Indonesia has, as an abundant archipelagic country. The area of mangrove forests in Indonesia is approximately 3,490,000 ha or equivalent to 21% of the world's mangrove forests. This research aims to analyze the community structure of the Boroko and Binuanga mangrove areas, North Bolaang Mongondow Regency, North Sulawesi Province. The research uses a survey method with a quantitative descriptive approach, namely a method of collecting data directly at the research location. The survey method was used to collect data in the form of mangrove identification, species diversity, species evenness and species uniformity in the mangrove area at the research location. The types of mangroves found in the Boroko and Binuanga mangrove areas consist of 7 species, namely Rhizophora apiculata, Rhizophora mucronata, Ceriops tagal, Bruguiera gymnorrhiza, Avicennia alba, Lumnitzera littorea, and Sonneratia alba. The results of the analysis of the diversity index, species richness and evenness of mangrove species in Boroko and Binuanga villages obtained a diversity index (H') value of 1.29-1.34, species richness (DMg) 1.01-1.23 and species evenness (E ) 0.68-0.71. The diversity of mangrove species in Boroko and Binuanga Villages is in the medium category, the evenness index (E) shows that the evenness of mangrove plants is stable and based on the species richness index criteria the two research locations are in the low species richness category.